One-Stage External Iliac Fixation Device and Bilateral Fascial and Groin Flaps Facilitate Abdominal Wall Closure after Posterior Sagittal Iliac Osteotomy in Cloacal Exstrophy - Giron, A. M.; Lopes, R. I; Guarniero, R.; Passerotti, C.; Srougi, M. (European Journal of Pediatric Surgery, 2011)
Repairing abdominal wall defects after cloacal exstrophy reconstruction always poses a challenge. Our proposal for repair consists of bilateral posterior iliac osteotomy and external iliac fixation with Schanz pins, together with abdominoplasty through bilateral groin flaps of skin and muscular aponeuroses, in a single staged procedure.7 patients (5 male and 2 female; mean age 3.1 years) with cloacal exstrophy underwent reconstructive surgery at our institution. Cloacal exstrophy reconstruction was performed in 3 stages, whenever possible. In Stage 1, the intestinal tract is separated from the hemi-bladders; the small colon is tubularized (colorrhaphy) with an opening on the left flank. The hemi-bladders are joined and the pathology is converted into classic bladder exstrophy, followed by primary repair (cystorraphy). At this stage, closure of the abdominal wall is made by groin flap plasty, following bilateral posterior iliac osteotomy with an external iliac fixator. Stage 2 consists of bladder augmentation and the management of urinary continence. Stage 3 is genitoplasty. The aim of this study was to demonstrate our results for the first stage.After a mean follow-up of 7 years, closure of abdominal wall was found to be excellent and successful in all 7 patients. Their abdominal walls are strong and solid, with no retraction, fistula or eventration.The association, in a single stage, of a posterior osteotomy with an external iliac bone fixator and bilateral groin flaps for the closure of soft tissue defects of the abdominal wall in cloacal exstrophy appears to be a safe and cosmetically acceptable alternative technique.
Keywords: bladder exstrophy; cloaca; iliac osteotomy